(untitled) (International Journal of Technology and Management Research, 2020)
The study examined Neglected and Underutilized Crop Species (NUCS) in two agro-ecologically diverse zones in Ghana with the view to highlighting the varieties, their important benefits and uses among rural households in the Upper Afram and Upper Dayi basins. Qualitative data was gathered from two hundred and seventy-one (271) respondents in six farming communities within the middle belt of Ghana through focused group discussions, interviews and questionnaires. A total of one hundred and twelve (112) NUCS were identified during the study. The diversity of NUCS in the study areas provide an indication of the existence of a valuable plant resource that can be exploited to help address food inadequacy challenges among rural households within the Upper Afram and Upper Dayi basins. Apart from their use as food, medicine, dyes, soap making, fuel wood and livestock feed, some NUCS found within the study basins play very important roles in the cultural practices and traditional ceremonies. These findings demonstrate the untapped potential of NUCS in addressing food and nutritional insecurity among rural households in the country. Institution of regular NUCS focused food fairs at the local (village), district and regional levels to promote local dishes prepared from the indigenous food crops; as well as increased NUCS related research are recommended. Citation: F. Baa-Poku and I. K. Asante. Use of Neglected and Underutilized Crop Species (NUCS) in some farming communities in the Upper Afram and Upper Dayi River Basins in Ghana, 2020; 5(2): 48－63. Received: April 3, 2020 Accepted: June 30, 2020